Pengaruh Kualitas Pelayanan dan Kepuasan Pasien Terhadap Loyalitas Pasien Rawat Jalan di Rumah Sakit Muhammadiyah Palembang - Nadia, Zahira Shafa; Rahayu, Sri; Puspasari, Mardiana (PT Maju Malaqbi Makkarana, 2025)
This study aims to determine the Influence of Service Quality and Patient Satisfaction on Outpatient Loyalty at Muhammadiyah Hospital Palembang. This study used 100 samples, the sampling technique used incidental sampling technique (Accidental Sampling). The type of research used is associative, the data used are primary and secondary data. Data collection techniques used are questionnaires and documentation. The analysis technique used is Multiple Linear Regression analysis, F Test, t Test and Determination Coefficient with a significance level of 10%. The results of the Multiple Linear Regression analysis of the variables of Service Quality and Patient Satisfaction have a positive influence on Patient Loyalty. The results of the study indicate that there is an influence of Service Quality and Patient Satisfaction together on Patient Loyalty at Muhammadiyah Hospital Palembang.